Equipment for the Production of Wood-Polymeric Thermal Insulation Materials; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Saldaev V. A. Vladimir; Prosvirnikov D. B. Dmitry; Stepanov V. V. Vladislav; Sadrtdinov A. R. Almaz; Kapustin A. N. Aleksey Nikolaevich (2016, 2016)
Title screen